Özgürlük kavramının canlandırma sineması kullanılarak tartışılması - Balki, Ozan (My University, 2010)
Canlandırma sineması, kullanılabilecek teknikler açısından çok esnek bir anlatım biçimidir. Bunun, avantajı olduğu kadar dezavantajları da vardır.Canlandırma film oluşturulurken dikkat edilmesi gereken en önemli konulardan biri görsel bütünlüğün korunmasıdır. Birden fazla tekniğin kullanıldığı filmlerde bunun sağlanması daha da zorlaşmakta bazen de, tarz olarak birbirinden tamamen farklı sahneleri aynı filmde görmek mümkün olmaktadır. Canlandırma filmlerin, “live action” filmelere göre maliyetleri ve yapım süreleri daha fazladır. Burada en önemli amacım; bir öğrenci filmi bütçesini aşmadan, filmi bitirmenin yolunu bulmaktı. İş yükünü ve harcanan zamanı minimuma indirecek farklı teknikleri sahnelere dağıtırken, aynı zamanda da sahnelerin görsel bütünlüğünü korumakta gerekliydi. Bu farklı tekniklerin, tek bir anlatı içinde ortak olarak kullanıldığı durumların iş yükünü hafifletmesi yanında, sahnedeki duygu ve atmosfer değişimlerinin vurgulanmasında da oldukça önemli rolü vardır. Yapım aşamalarının sonuna geldiğinde artık filmde kullanılacak teknikleri belirlemenin zamanı gelmişti. Rotoskop tekniği, başlarda çok zahmetli bir yöntem olmasına rağmen, teknolojinin gelişmesiyle artık özel efekt programları yardımıyla taklit edilebilmektedir. Özgürlük canlandırma filminde, yoğunlukla rotoskop tekniği olmak üzere, üç boyutlu canlandırma ve cell animation teknikleri üzerinde yoğunlaşıldı. Fikir aşamasından başlayarak üretim sürecinin sonuna kadar karma teknikle hazırlanmış canlandırma filmin, hangi evrelerden geçtiği, tekniklerin birlikte kullanımının avantajları üzerinde durmaktadır.

Animation is a flexible expression way in terms of the techniques that can be used. It has advantages as well as disadvantages. While making a film, protecting the visual integrity is one of the most important subjects which must be paid attention. It is harder in the movies which more than one technique are used in, and also sometimes it is possible to see different types of scenes. The costs and the lenght of making of the animation are more than live action films. My target was in this subject is to find a way to end the film before exceeding the budget of a student film. While distributing the techniques to the scenes to have the minimum workload and the minimum time which is spent, it was necessary to save the visual integrity of the scenes. Animated cinema is quite a flexible way of expression in terms of the techniques that can be made use of. This way of expression has some both advantages and disadvantages. One of the most important points while generating a film is to keep the visual integrity. In the production of films in which more than one technique is used, it is more difficult to keep the visual integrity, and what is more, it is sometimes possible to see stylistically different stages in one and the same film. As I landed up the processing phases, it was time to assign the technics which will be used in movie.Despite it was considered a difficult method once, Rotoscoping is now can be imitated by special effect programs as our technology develops. I focused on 3D animation and cell animation technics while mostly using Rotoscoping. Compared to “live action” films, animated films are more costly and the duration of production is longer. In this production, the most important goal I had was to find a way to make a film within the limits of a student’s budget. Besides keeping the visual integrity of the stages, it was also necessary to draw upon different techniques that may be of help to minimize the work load and time to spend in different stages.
Keywords: Beyaz Perde; Sinema